Die one weier om te verdwyn - Roux, J. H. le (Verbum et ecclesia, 2000)
The old refuses to disappear This article deals with some aspects of presentday Pentateuchal research. It is stated that although the basic elements of nineteenth century Pentateuch criticism still prevail, the study of the Pentateuch has also changed in many ways. Pentateuchal studies did not, however, escape the hermeneutical insights of the twentieth century. This opened up new ways of understanding and evaluating reseach results. More emphasis is also being laid on the final text and the forces which shaped the final form of the Pentateuch. One important paradigm shift is the rejection of the Davidic-Solomonic era as the earliest context of the Pentateuch in favour of the neo-Assyrian time. During this period the Pentateuch originated, and was meant as resistence against the neo-Assyrian powers.